1984
DOI: 10.1351/pac198456091289
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and kinetic investigations of conjugated biradical intermediates

Abstract: -Several reactive biradical intermediates of photochemical reactions were monitored directly in solution by the technique of kinetic and time-resolved spectrographic laser flash photolysis, and identified with the aid of low-temperature epr and optical spectroscopy, semiempirical calculations, as well as conventional steady-state analyses of product distributions. The focus of this report is on a number of mechanistic questions particular to the behaviour of biradicals and the experimental response obtained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 3 publications
2
41
0
Order By: Relevance
“…The calculated BRC, HLG, STG and eigen values of the stability matrix for molecules have been given in Table . According to Wirz, a molecule can be a biradicaloid when the STG lies around 2–24 kcal/mol . From Table , all these molecules have been found around 24 kcal/mol of STG, except 1a and 3 are having 26.99 kcal/mol and 27.92 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…The calculated BRC, HLG, STG and eigen values of the stability matrix for molecules have been given in Table . According to Wirz, a molecule can be a biradicaloid when the STG lies around 2–24 kcal/mol . From Table , all these molecules have been found around 24 kcal/mol of STG, except 1a and 3 are having 26.99 kcal/mol and 27.92 kcal/mol, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…The electronic excitations of CSQ molecules are underestimated by TDDFT methods, and the reason may be due to presence of some diradical character (DC) in these molecules . Various methods are available to estimate the DC . One of the criteria to estimate DC is Wirz singlet‐triplet energy gap.…”
Section: Resultsmentioning
confidence: 99%
“…One of the criteria to estimate DC is Wirz singlet‐triplet energy gap. According to Wirz, when the energy gap between singlet and triplet states is around 2 to 24 kcal mol −1 in a molecule, the molecule is said to be a diradical . We have estimated singlet‐triplet gap (E S‐T ) from singlet and triplet optimized geometries for both the series (NSQ and CSQ) as per Equation and are estimated E S‐T shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been suggested for estimating the BRC 88–91. Wirz had suggested that a molecule can be said to be a biradical if the splitting between the singlet (S 0 ) and triplet (T 1 ) is around 2–24 kcal/mol 88.…”
Section: Resultsmentioning
confidence: 99%
“…Several methods have been suggested for estimating the BRC 88–91. Wirz had suggested that a molecule can be said to be a biradical if the splitting between the singlet (S 0 ) and triplet (T 1 ) is around 2–24 kcal/mol 88. On the other hand the percent BRC can also be estimated by using the method suggested by Nakano et al 92–95.…”
Section: Resultsmentioning
confidence: 99%